Peningkatan Literasi Gizi Atlet Sepak Bola Remaja melalui Edukasi Berbasis Aplikasi Smartwebcalc di Maguwoharjo Football Academy: Improving Nutritional Literacy of Young Football Athletes through Smartwebcalc Application-Based Education at Maguwoharjo Football Academy - Yuni Afriani; Desty Ervira Puspaningtyas; Siska Puspita Sari; Nurhadi Wijaya; Jessica Paskalina; Reggy Chrismanta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Balanced nutrition plays a vital role in supporting the performance of young football athletes, especially adolescents who are experiencing rapid growth and intensive training demands. This community engagement program aimed to strengthen the nutritional literacy and meal-planning skills of remaja football athletes by using the Smartwebcalc web-based application at Maguwoharjo Football Academy, Sleman. The program included sessions on balanced nutrition, hands-on training in application, guided menu-planning simulations, and evaluations using pre- and post-tests. A total of 22 U-15 athletes took part in the activities. The pre-test results showed that 54.54% of participants scored ≥70, while only 9.09% achieved a perfect score of 100, indicating that although basic nutritional knowledge was present, it was not yet evenly distributed, particularly in understanding energy needs and selecting appropriate foods for training. In the post-test, the proportion of athletes scoring ≥70 remained at 54.54%, while the number of perfect scores increased to 13.64%, suggesting improved comprehension among some participants. Overall, the program contributed positively to enhancing nutritional awareness, promoting healthier eating habits, and encouraging the use of digital tools among young athletes. The Smartwebcalc application proved an effective medium for learning about nutrition and holds strong potential for replication in other sports academies.